Análisis de la comunicación digital estratégica de la página Chone Resurge Por Ti en la plataforma Facebook - Paguay Zambrano, María de los Ángeles (2021)
Currently the globalized world has become matter of public interest, it can be seen that the migration of public or private organizations towards digitization is imminent, this in order to obtain two-way communication with society, is why Through this investigative work it is intended to analyze the strategic digital communication of the page "Chone Resurge por Ti" on the Facebook platform. Which was analyzed through a mixed methodology with qualitative and quantitative approaches, which were applied based on the direct observation technique supported by an observation sheet. In addition, based on the interview technique, a questionnaire was applied to the Communication Directorate of the GAD Chone, which allowed to show the communication strategies, the target audience, the content of greatest interest, among other points that weight the page as a source of truthful information for the community in general, since it promotes its care and inclusion. This is how it is possible to see that the fan page handles a clear and concise language, in such a way that it is reflected in the interaction of the contents causing acceptance, feedback and, most importantly, user loyalty.